Interpersonal Cognitive Distortions, The Level of Anxiety and Hopelessness of University Students - Aysel Esen ÇOBAN; Neslihan Güney KARAMAN (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The purpose of this study is to determine university students’ interpersonal cognitive distortions, the level of anxiety and hopelessness and to find out the differences of gender and age in terms of students’ interpersonal cognitive distortions, the level of anxiety and hopelessness. Method: To this study 287 (%78.6) female, 78 (%21.4) male, total 365 university students participated. Hopelessness Scale, anxiety Inventory, and interpersonal cognitive distortions Scale were used to collect data and the data was analyzed by using SPSS. Descriptive statistics (mean and standard deviation) and One Way ANOVA was used to analyze the data. Results: The results of the analyses showed that male and female university students who are age of 21-25 years old are relatively higher than other age groups in their interpersonal cognitive distortions, the level of anxiety, and hopelessness. There were no significant differences between male and female students in terms of interpersonal cognitive distortions, the level of anxiety and hopelessness. In other words, male and female university student’s interpersonal cognitive distortions, the level of anxiety and hopelessness were not significantly different and both male and female students who are age of 21-25 years old have relatively higher means in terms of interpersonal cognitive distortions, the level of anxiety and hopelessness. Conclusion: The results were not consistent with the literature. The reason of this could be that this study was made on healthy populations that are not diagnostic patients and this study was made on the students who continue to the foundation university. (Journal of Cognitive Behavioral Psychotherapy and Research 2013, 2: 78-88) [JCBPR 2013; 2(2.000): 78-88]